Literature Review: Analisis Implementasi Fungsi-Fungsi Manajemen dalam Organisasi Kesehatan: Konsep, Karakteristik, dan Tantangan - Pandini, Sapitri; Mirza, Rama; Agustina, Wintan; Hartono, Budi (Innovative: Journal Of Social Science Research, 2025)
According to information cited on Monday, October 26, 2020, from the Worldometers website, there are presently 43.3 million Covid-19 instances worldwide. Of that total, 31.8 million individuals have been deemed cured, while over 1.1 million people have died. Currently, there are 10.2 million active cases, of whom 10.1 million are in moderate condition and 77,726 are in acute or critical condition. With almost 8 million cases, the United States (US) continues to record the highest overall number of cases. various negative impacts can arise on individual organizations and the goals to be achieved When management functions are not implemented properly, there are no clear goals in the organization, making decisions without a strong basis has the potential to cause fatal mistakes, Health management is the main key to improving the efficiency and quality of services in the health sector. This research examines the application of knowledge management and technology in health management, and its impact on the management of health services in various fields, including hospitals, primary care, and the industrial sector. Based on 25 journals reviewed, the research identified that knowledge management and advanced technologies such as telemedicine, blockchain, and prognostic systems play an important role in improving the quality of healthcare. In addition, the study also highlighted the challenges faced in the implementation of health management, such as gaps in knowledge, culture, and adequate infrastructure, as well as the influence of external factors such as the COVID-19 pandemic. The results show that while outcome-based management technologies and models have proven to be effective, challenges in implementation remain barriers that need to be overcome. Therefore, the development of more adaptive and technology-based management models is crucial to improve the efficiency and sustainability of the health system.